STRATEGI PENINGKATAN PELAYANAN PRIMA STUDI KASUS PADA BPJS KESEHATAN CABANG MAGELANG - Agustin Erna Purnamawati (MANAJEMEN DEWANTARA, 2021)
This study aims to define the appropriate strategy formulation to improve excellent service quality for the customers in the BPJS Kesehatan Branch of Magelang.The method of this research using the qualitative descriptive approach. The writer using SWOT analysis (Strength, Weakness, Opportunitis and Threats), IE (Internal External) Matrix, then QSPM (Quantitative Strategic Planning Matrix) which is an alternative method for determining priority of the strategy.The results of this study, the position of excellent service quality at BPJS Kesehatan Branch of Magelang based on the IE analysis is in Quadrant I (growth and develop), the value of the coordinate (3.31; 3.21). The result of SWOT matrix is in Quadrant I, it is shown on the coordinates of the x=1.47 and y=1.01. It means that the company is suggested to employ the strategy of aggressive. The results of the QSPM analysis show that there are 13 alternative strategies, which the majority of alternative strategy should be managed which are carried out by product development strategies, then followed by market penetration strategy. The highest TAS (Total Attractiveness Scores) value is in doing roleplay related to continuous excellent service to employees, followed by activities of gemba service (TAS value of 6,46).